“Things Unseen”: Urban (Dis)placement, Sacred Sensibilities, and Theological Vantage Points - Smith, R. Drew (Theology today, 2023)
This article explores the ways in which academic institutions in Pittsburgh have positioned themselves around local gentrification dynamics. It pays particular attention to academic facilitations of community-oriented analysis and engagement that attempts to counter gentrification's deformative and deracinating effects and that centers responsiveness to problems stemming from gentrification processes and dynamics as a theological or moral imperative toward seeking the good of the city.